CHARACTERIZING THE SHAFT DEFORMATION IN THE TISHINSKY MINE SUBJECTED TO SURFACE SUBSIDENCE - Smagambetov, Bekzhan (Nazarbayev University School of Mining and Geosciences, 2022)
Shafts play an important function in terms of safety and profitability throughout the life of a mining operation. The access shaft stability has always been a significant challenge in mining engineering, especially as mining depths have increased. Therefore, it is vital to determine the deformation and failure mechanisms of the about 970 m shaft in the Tishinsky mine where the main shaft has experienced major deformation together with surface subsidence. Driven by these reasons, the aim of this study is to characterize the ground deformations and movements in order to establish any relationship between the surface deformation and the shaft deformation. To this end, ground monitoring data were collected and analyzed. It was found that the shaft deformation was highly correlated with both horizontal and vertical surface displacement, especially for 2018-2019. The maximum deformation reached 0.07 m at the level about 600 m. However, the deformation decreased in 2020 after ground control measures were taken.
Keywords: Type of access: Gated Access; shaft deformation; Tishinsky mine